Walk 2. Alexandrovsky Boulevard. From the Museum of Local Lore to Strelka - Smirnova, Olga (project baikal, 2012)
A Drop of the Nile at Yenisei Water. The Krasnoyarsk Regional Museum of Local Lore (Dubrovinsky Street, 84)When Reading the Historians. A Trace of TalentThe Riverside Station. History and Present DayThe Krasnoyarsk Museum Center